Actor Collaboration in the Sae Hunt Program in Bandung City - Sukandi, Pipin (Decision, 2022)
This diary was developed to investigate how players relate to their cooperation in the Buruan SAE program in Bandung. Whatever the Bandung government undertakes in the administration of the Buruan SAE program, as well as everyone else participating in the food crisis. The Buruan SAE program is an integrated urban project implemented by the Bandung food and agriculture service (dispangtan) with the goal of addressing Bandung's food disparity. Regional government involvement through food and agriculture services, as well as civic engagement, are anticipated to ensure that the program runs smoothly and produces the desired results. This paper employs a qualitative method that combines descriptive analysis with secondary data retrieval from books, journals, papers, and websites about interactor collaboration in the Buruan SAE program in Bandung. This study aims to determine how to connect actors in the Buruan SAE program in Bandung to cope with the food crisis.